Rubella susceptibility in pregnant women and results of a postpartum immunization strategy in Catalonia, Spain. Issue 15 (8th April 2015) - Vilajeliu, Alba; García-Basteiro, Alberto L.; Valencia, Salomé; Barreales, Saul; Oliveras, Laura; Calvente, Valentín; Goncé, Anna; Bayas, José M.
Highlights Rubella postpartum vaccination is an opportunity to protect women of childbearing age. Higher rubella susceptibility in the youngest age groups and in immigrant women. Relevance of identification and postpartum immunization of rubella susceptible women. Increased MMR coverage reinforces to achieve eliminating endemic rubella and measles.